Standstill corrosion of the BNi-2/316L brazing joints in a stirling engine. (April 2023) - Zhang, H.Y.; Xu, W.; Zhu, T.Y.; Qu, S.; Dong, C.; Wang, X.G.; Zhang, Z.F.
Highlights: Stand still corrosion of the BNi-2/316L brazing is reported for the first time. The leakage is due to combined effects of standstill corrosion and crevice corrosion. The wide brazing clearance and nitrogen borides could promote the corrosion. Abstract: A stirling engine was stored for about two years. When the engine was started, the cooler in the engine was found leaked, which affects the normal operation of the entire equipment. After dismantling, brazing seems between the cooling tubes and the cylinder were detected leaked by air pressure tests. The leaked sites were further determined at the diffusion zones of the brazing joints by the X-ray tomography and microscopic inspections. The crevice penetrated the diffusion zones, where chromium in the matrix depleted due to the formation of chromium borides. Considering the storage environment and the corrosion characteristics, the cause of the leakage is confirmed at the combined effect of standstill corrosion and crevice corrosion in the Cl - containing water. In addition to the failure cause, the wide brazing clearance and formation of nitrogen borides are considered to be two factors that promoted corrosion. Based on the above analysis, suggestions are proposed to prevent recurrence of corrosion and improve the corrosion resistance of the BNi-2/316L brazing joint.